Cerebrospinal Fluid Cytokines in Multiple System Atrophy: a Cross-Sectional Catalan MSA Registry Study - Compta, Y (2019)
Introduction: Neuroinflammation is a potential player in neurodegenerative conditions, particularly the aggressive ones, such as multiple system atrophy (MSA). Previous reports on cytokine levels in MSA using serum or cerebrospinal fluid (CSF) have been inconsistent, including small samples and a limited number of cytokines, often without comparison to Parkinson's disease (PD), a main MSA differential diagnosis. Methods: Cross-sectional study of CSF levels of 38 cytokines using a multiplex assay in 73 participants: 39 MSA patients (19 with parkinsonian type [MSAp], 20 with cerebellar type [MSAc]; 31 probable, 8 possible), 19 PD patients and 15 neurologically unimpaired controls. None of the participants was under non-steroidal anti-inflammatory drugs at the time of the lumbar puncture. Results: There were not significant differences in sex and age among participants. In global non-parametric comparisons FDR-corrected for multiple comparisons, CSF levels of 5 cytokines (FGF-2, IL-10, MCP-3, IL-12p40, MDC) differed among the three groups. In pair-wise FDR-corrected non-parametric comparisons 12 cytokines (FGF-2, eotaxin, fractalkine, IFN-α2, IL-10, MCP-3, IL-12p40, MDC, IL-17, IL-7, MIP-1β, TNF-α) were significantly higher in MSA vs. non-MSA cases (PD + controls pooled together). Of these, MCP-3 and MDC were the most significant ones, also differed in MSA vs. PD, and were significant MSA-predictors in binary logistic regression models and ROC curves adjusted for age. CSF levels of fractalkine and MIP-1α showed a strong and significant positive correlation with UMSARS-2 scores. Conclusion: Increased CSF levels of cytokines such as MCP-3, MDC, fractalkine and MIP-1α deserve consideration as potential diagnostic or severity biomarkers of MSA.